Caffeine during exercise in the heat: Thermoregulation and fluid-electrolyte balance - Del Coso, J.; Estevez, E.; Mora-Rodriguez, R. (Medicine & Science in Sports & Exercise, 2009)
Purpose: To investigate the effects of caffeine ingestion on thermoregulation and fluid-electrolyte losses during prolonged exercise in the heat.